Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression - Staudt, Michael; Mir, Celine; Joffre, Richard; Rambal, Serge; Bonin, Aurelie; Landais, Damien; Lumaret, Roselyne (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.
Keywords: basal emission rate; chemotaxonomy; chemotypes; Evergreen oaks; genetic introgression; isoprene; Monoterpenes; VOC (volatile organic compound) emissions.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.